Clinical and radiological characteristics of the course of the newly diagnosed tuberculosis spondylitis in adults and the effectiveness of the main course of antimycobacterial therapy - О. М. Raznatovska; V. V. Bezdenezhnyi; V. I. Mozolyuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Study objective – set the frequency of detection of the newly diagnosed tuberculous spondylitis, the features of clinical and radiological manifestations of it and the effectiveness of the main course of antimycobacterial therapy.